ความชุกของการขาดหายของโปรตีนพีเทนในผู้ป่วยโรคมะเร็งเต้านมชนิดทริปเปิลเนกาติพ (ชนิดที่ไม่แสดงถึงฮอร์โมนเอสโตรเจน ฮอร์โมนโปรเจรเตอโรนและเฮอร์ทู) ในประชากรของประเทศไทย - ทิวา เกียรติปานอภิกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
INTRODUCTION: Currently a definitive marker for positive selection of the triple-negative breast cancer (TNBC) remains unavailable. PTEN expression may play an important role in TNBC aggressive phenotype. We sought PTEN expression in TNBC in our institute. OBJECTIVE: The primary objective is to determine the prevalence of PTEN loss in TNBC tumor tissue. We found an association between clinical parameters and PTEN expression. METHODS: Female TNBC patients who received treatment were identified. Tissue microarrays were constructed and we used anti-PTEN clone 28H6 to determine the level of PTEN protein. RESULTS: There were 78 TNBC patients with adequate tumor tissue available. Our cohort found mostly grade 3, and Ki - 67 > 30% , which was not different from other studies. Thirty percent (24 of 78) had undetectable PTEN. In PTEN –negative patients, the average age was 50.3 years. Loss of PTEN expression was associated with tumor size (>2 cm) (79.3% vs 70.4%), lymphovascular invasion (52.6%vs46.8%), lymph node involvement (54.2% vs 35.1%). Time to recurrence was shorter in the PTEN negative group (30 months vs not reach) (Odd Ratio (OR) = 0.61, 95%CI = 0.24,1.58, P=0.22). CONCLUSION: One – third of Thai TNBC patients have PTEN loss. Our data indicates a poorer prognosis in TNBC with PTEN loss. Further study in larger population and longer time of follow up is warranted.